(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: One of the most prevalent kidney disorders in children is nephrotic syndrome (NS). It is characterized by massive proteinuria, hypoalbuminemia, and edema. Objective: To study demographic and clinical characteristics of NS, hospitalization characteristics and the occurrence of complications during hospitalization, with comparison of some characteristics between hospitalized and non-hospitalized patients. Methods: Ninety NS patients, aged 1 to 15 years, who were either admitted to the Pediatric Ward of Al-Imamein Al-Kadhimein Medical City or followed in the Pediatric Nephrology Consultation Clinic between April 1, 2021, and May 31, 2022, were included in this prospective observational study. The main parameters studied were demographic and clinical characteristics of NS, complications during hospitalization, with comparison of some characteristics between hospitalized and non-hospitalized patients. Results: Male patients made up the majority (66.7%), of age group 5.1-10 years (44.4%), living in urban areas (70%), disease onset age of ?5 years (66.7%), disease duration of >4 years (35.6%), and those with frequent relapses being the most prevalent kind (44.4%). Most patients stay in the hospital for 4-7 days (68.5%) and are admitted to the hospital an average of 45.6% of the time per year. The most prevalent complications were anasarca (76%), acute kidney injury (AKI) (17.8%), and scrotal edema (15.1%). Comparison between hospitalized and non-hospitalized children with NS, detected no significant difference according to age of patients, gender, age of onset, type of NS, residency and duration of disease. Conclusion: Complications of NS, especially serious ones during hospitalization, are not uncommon. High index of suspicion for complications, not to miss them. Keywords: nephrotic syndrome, hospitalization, children Citation: Shaker AT, Ali SH, Ali LQH. Hospitalization of children with nephrotic syndrome. Iraqi JMS. 2024; 22(1): 65-73. doi: 10.22578/IJMS.22.1.8